Analisis Hubungan Faktor Kehamilan dengan Kejadian Pre-Eklamsia pada Ibu Hamil di Curahnongko - Junierna Junierna; Lisus Setyowati; Iit Ermawati (ARTERI : Jurnal Ilmu Kesehatan, 2022)
One of the main causes of mother’s death in Indonesia is Pre-eclampsia/eclampsia. The causes of pre-eclampsia still unknown certainly. The symptomps of pre-eclampsia are hypertension, edema dan proteinuria which can caused by pregnancy on more than 20 weeks. The aims of this research was analysed of relationship between pregnancy factors with pre-eclampsia on pregnant woman in Curahnongko Health Center. This research was quantitative, used cross sectional approach. Also used total sampling technique to get 35 respondents. The analysis result was gotten if there was relationship between relationship between pregnancy factors with pre-eclampsia on pregnant woman in Curahnongko Health Center. From multivariate analysis, the dominant factor which related to pre-eclampsia was history of hypertension. The analysis result could known from the history of hypertension was 7.671, it meant the history of hypertension had higher risk to pre-eclampsia than other pregnancy factors. Hopefully for pregnant woman to do ANC more routine and be aware to hypertension during pregnancy which is dominant cause to pre-eclampsia, to attain plenary health of mother and baby.